Descriptive Memoir of Ministry of Law as on 1st October , 1955 - Planning Commission (Planning Commission, 1955)
Advice to various departments of the Government of India on all constitutional and legal matters, including interpretation of the Constitution and other laws scrutiny of statutory rules and orders, conveyancing, conduct of all cases in the Supreme Court on behalf of the Central and the State Governments and legal proceedings in which Government is concerned, participating preparation of case for the opinion of Attorney General of India and the Solicitor General after the cases are stated.
Government of India Cabinet Secretariat O. & M. Division